Exploring the perceptions of domestic violence interventions among women using MOSAIC services in Cape Town - Birungi, Sarah Okedi (2020)
This study was undertaken to explore perceptions of domestic violence interventions among women using the services of MOSAIC in Cape Town. The study sought to obtain the women’s expectations of the services at MOSAIC, the perceived beneficial and non-beneficial aspects of the services at MOSAIC as well as the suggestions towards the improvement of services at MOSAIC. The findings of the study could facilitate prioritisation and implementation of services that meet the needs of the clients and the improvement of services at MOSAIC. In this qualitative study, face-to-face interviews were conducted among 30 clients of MOSAIC who had attended four or more counselling sessions. The female victims of domestic violence from heterosexual relationships were aged between 19 to 70 years. The participants were selected using a non-probability, purposive sampling method. Data was collected using an interview schedule and recorded with a digital voice recorder. The interviews were conducted at a private venue in Parkwood and MOSAIC’ssatellite offices at Phillipi and Mitchells Plain. Tesch, (1990) eight steps of data analysis were used for analysing data. The findings of the study indicated that receiving counselling was the women’s main expectation of MOSAIC services. Other expectations included receiving emotional support and improved safety in the aftermath of the abuse. The perceived helpful aspects of MOSAIC services included; the availability of the social workers to offer support, the therapeutic relationship between the social workers and the clients, providing clarity and guidance through decision making, improved wellbeing, improved social relations, improved empowerment, supportive counselling and meeting safety needs. The unhelpful aspects of the services at MOSAIC including inconsistent working hours and a poor counselling environment were raised by participants who received assistance from one of the satellite offices. The suggestions for improvement of services at MOSAIC included offering privacy during counselling, co-treatment of substance abuse and domestic violence as well as interventions for different client groups. Other suggestions included increased resources for DV interventions, increased awareness about services at MOSAIC and assisting DV victims to obtain employment. The final suggestions for disclosure of abuse and help-seeking were extended to women in abusive relationships